Pengembangan Budaya Sekolah Berprestasi: Penanaman Nilai Etos Berprestasi - Pratiwi, Ageng; Roesminingsih, Erny; Karwanto, Karwanto (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Senior High School Muhammdiyah 10 Surabaya is a school that dares to make a different curriculum from Diknas. It was rejected because it did not fit the existing curriculum. In its first year, the school receives two classes of students. This achievement soared in the second year. Second year there are five classes. The curriculum used at Senior High School Muhammadiyah 10 Surabaya is called